Palazzo : a novel [large type] - Steel, Danielle (Random House Large Print, 2023)
After her parents perish in a tragic accident, Cosima Saverio assumes leadership of her family's haute couture Italian leather brand. While navigating the challenges of running a company at twenty-three, Cosima must also maintain the four-hundred-year-old family palazzo in Venice and care for her younger siblings: Allegra, who survived the tragedy that killed their parents with scars and a spinal injury, and Luca, who has a penchant for wild parties, pretty women, and poker tables. Cosima navigates her personal and professional challenges with a wisdom beyond her years, but her success has come at a cost: Her needs are always secondary. She's married to the business, and her free time is given to those who rely on her...until she meets Olivier Bayard, the founder of France's most successful ready-to-wear handbag company. A brief conversation on her palazzo's terrace turns into a tour of the Saverio workshop, and, fifteen years after her parents deaths, Cosima has found a confidant. Now the business is financially stable and generating enough income for the Saverios to live comfortably. Then Luca loses a hefty sum at the casino, and his debt must be repaid with money or his life. Cosima, forced to bail him out, is given an impossible choice: List the palazzo, sell a third of the family business, or let Luca fend for himself. But is there another way to save everything she has fought for before it goes up in flames? --